2018
DOI: 10.3390/su10020375
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Quality Management Practices to Sustainability Performance of Vietnamese Firms

Abstract: This study seeks to investigate the relationship between quality management practices and sustainability performance as well as the moderating effects from quality management implementation timeline, type of industry, and firm size on this relationship. Data were collected from enterprises in Vietnam from July 2016 to March 2017. Based on a sample of 144 valid responses, empirical results indicate that quality management practices have mixed impacts on economic performance and environmental performance, while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
60
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(68 citation statements)
references
References 79 publications
(186 reference statements)
5
60
0
3
Order By: Relevance
“…Two types of studies were identified, according to their main outcomes: those establishing a negative relationship between QM and EM (see Table 3), which are in the minority (e.g., [69][70][71][72]), and those reporting positive results (see Table 4), stating that QM is closely related to the promotion of EM, and innovation in EM in particular (e.g., [24][25][26][27][28]35,36,42,[73][74][75][76][77][78][79][80]). Other authors, such as Steiber and Alänge [73], point out that while some aspects of QM could actually bring benefits to EM (e.g., environmental innovation), the question of whether QM as a whole does so is not very clear. The majority of the papers establishing a negative relationship between QM and EM have suggested that QM tools and methodologies-especially those of ISO 9001-tend to increase the formalization and systematization of processes in organizations, hindering a set of aspects related to EM, such as green innovation, as they increase bureaucracy [63].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two types of studies were identified, according to their main outcomes: those establishing a negative relationship between QM and EM (see Table 3), which are in the minority (e.g., [69][70][71][72]), and those reporting positive results (see Table 4), stating that QM is closely related to the promotion of EM, and innovation in EM in particular (e.g., [24][25][26][27][28]35,36,42,[73][74][75][76][77][78][79][80]). Other authors, such as Steiber and Alänge [73], point out that while some aspects of QM could actually bring benefits to EM (e.g., environmental innovation), the question of whether QM as a whole does so is not very clear. The majority of the papers establishing a negative relationship between QM and EM have suggested that QM tools and methodologies-especially those of ISO 9001-tend to increase the formalization and systematization of processes in organizations, hindering a set of aspects related to EM, such as green innovation, as they increase bureaucracy [63].…”
Section: Resultsmentioning
confidence: 99%
“…For example, in their study carried out in Brazil, de Sousa Jabbour et al [11] found that QM is a relevant antecedent for the EM maturity of an organization. Similarly, based on a sample of 144 responses from Vietnamese companies, Nguyen et al [73] found that QM practices have various positive impacts on EM (e.g., environmental performance). These authors identified four QM practices that have a significant positive impact on EM and sustainable development: senior management support, design process, data and reporting quality, and continuous improvement.…”
Section: Resultsmentioning
confidence: 99%
“…Quality management practices have been shown to have positive impact on social performance, while the impacts on economic and environmental performance were mixed, requiring it to be embedded into dedicated competition and Corporate Social Responsibility strategies. The four quality management practices having the most significant positive impact on sustainability performance were top management support for quality management, design for quality, quality data and reporting, and continuous improvement [8].…”
Section: From An Agricultural To An Industrial Economymentioning
confidence: 99%
“…Unfortunately, there are even negative developments being found, related for instance to clean water (SDG 6), sustainable cities and communities (SDG,11), responsible consumption and production (SDG 12), and life below water (SDG 14) and on land (SDG 15) [5][6][7][8].…”
Section: Introduction mentioning
confidence: 99%
“…Importance of quality management and its impact on the performance of businesses has been widely researched and plethora of literature is available on this topic (Ali, 2014;Czajkowska & Stasiak-Betlejewska, 2015;Fotopoulos & Psomas, 2010;Jaafreh & Al-abedallat, 2012;Nguyen, Phan & Matsui, 2018). Simultaneously many researchers, (Gavrea, Ilies & Stegerean, 2011;Karia & Wong, 2013;Karia, Wong, Asaari & Lai, 2015;Kraja & Osmani, 2015), have emphasized the importance of service competencies as a tool to get competitive advantage for better performance, but the direct impact of quality management practices on the integration capability of Logistics Service Providers (LSPs) is not duly researched.…”
Section: Introductionmentioning
confidence: 99%